1997
DOI: 10.1111/j.1365-2621.1997.tb12235.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spray‐drying, Drum‐drying and Freeze‐drying for β‐Carotene Encapsulation and Preservation

Abstract: Pure b-carotene was encapsulated in 25 Dextrose Equivalent maltodextrin by three drying processes (spray, freeze and drum). Stability was studied at 11% and 32% RH and 25°C, 35°C and 45°C. No significant influence of %RH was observed on the retention of b-carotene. Oxidation followed first order kinetics with an initial fast first order reaction followed by a second much slower first order reaction period. Although drum-drying caused more initial loss in drying, the lower surface carotenoids and larger particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
195
1
19

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(246 citation statements)
references
References 13 publications
(16 reference statements)
18
195
1
19
Order By: Relevance
“…Pode ter ocorrido também oxidação de ácido ascórbico, e em menor extensão, escurecimento não enzimático devido hidrólise de sacarose comercial, conforme previamente observado e discutido por AMMU et al 3 em estudo similar com manga liofilizada. A oxidação de pigmentos afetando a cor durante o armazenamento tem sido investigada por outros autores 12,14,16 , por ser um atributo sensorial de muita importância para a aceitabilidade do produto pelo consumidor, e que muitas vezes está relacionada com a degradação de constituintes que têm valor nutricional e que podem promover gosto desagradável no produto. Em relação ao tamanho de partícula, os resultados obtidos indicaram que os tratamentos diferiram significativamente (p < 0,05), cujas médias encontram-se expostas na Tabela 5.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Pode ter ocorrido também oxidação de ácido ascórbico, e em menor extensão, escurecimento não enzimático devido hidrólise de sacarose comercial, conforme previamente observado e discutido por AMMU et al 3 em estudo similar com manga liofilizada. A oxidação de pigmentos afetando a cor durante o armazenamento tem sido investigada por outros autores 12,14,16 , por ser um atributo sensorial de muita importância para a aceitabilidade do produto pelo consumidor, e que muitas vezes está relacionada com a degradação de constituintes que têm valor nutricional e que podem promover gosto desagradável no produto. Em relação ao tamanho de partícula, os resultados obtidos indicaram que os tratamentos diferiram significativamente (p < 0,05), cujas médias encontram-se expostas na Tabela 5.…”
Section: Resultsunclassified
“…A secagem por spray drying tem sido aplicada a vários alimentos líquidos e pastosos, devido ao rápido contato dos mesmos com altas temperaturas, minimizando danos térmicos, além da alta produção e baixo custo em comparação com a liofilização 1,5,14,15,21,27,34 .…”
Section: Introductionunclassified
“…Carotenoids determination Total amounts of carotenoids in the sample powders were determined according to a method described by Desobry et al (1997). Fifty mg of powder were dispersed in 2.5 mL water in a test tube, and then 25 mL hexane was added.…”
Section: Preparation Of Emulsions and Microencapsulated Powdersmentioning
confidence: 99%
“…Modified and hydrolyzed starch, maltodextrin (MD), and gum acacia (GA) are common wall materials for use in spray drying encapsulation of food ingredients (Desai and Park 2005). The shelf lives of α and β-carotene were reportedly increased by spray drying using MD with different dextrose equivalent values (Wagner and Warthesen 1995;Desobry et al 1997). Loksuwan (2007) used modified/native tapioca starch and MD to increase the stability of microencapsulated β-carotene.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation of β-carotene with maltodextrin is another means to protect carotenoids from oxidation (Wagner and Warthesen, 1995;Desobry et al, 1997). Studies indicated that the higher dextrose equivalent (DE) starch forms a tighter and more gas impermeable matrix and provides a greater carotenoid stability.…”
Section: Blanching Effect On Carotenoid Contentmentioning
confidence: 99%